The transformation and reconciliation of Malaysia speeches of Prime Minister Najib Tun Razak, 2013 - Mohd. Najib Tun Haji Abd. Razak Dato' Seri 1953- (Jabatan Penerangan Malaysia, 2014)
[This book] is a compilation of speeches of the Honourable Dato Sri Mohd Najib Tun Razak, the sixth Prime Minister of Malaysia. It focuses mainly on the development of human capital and strengthening integrity in an effort to build a prosperous country.